Russia in the Nineteenth Century : Autocracy, Reform, and Social Change, 1814-1914. - Polunov, Alexander (New Russian history., 2005)
This covers the history of Russia from the defeat of Napoleon to the eve of World War I. It is the first such work by a post-Soviet Russian scholar to appear in English. It examines the decay of the two central institutions of tsarist Russia: serfdom and autocracy; the major social groups and how they reacted to the Great Reforms.